2012
DOI: 10.3109/02770903.2011.652328
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Leisure-Time Physical Activities and Asthma Symptoms among 10- to 12-Year-Old Children: The Effect of Living Environment in the PANACEA Study

Abstract: The inverse relationship between asthma symptoms and leisure-time physical activity in the rural environment and the lack of an association between asthma symptoms and organized sports-related activities should draw the attention of public healthcare authorities. Their efforts should focus on the planning of a sustainable natural environment, which will promote the physical health of children and reduce the burden of childhood asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 36 publications
0
20
0
1
Order By: Relevance
“…Indeed, only 11% of adolescents living in rural areas and 9% of those living in urban, reported to have a good adherence (namely reaching the highest tertile of the index) to the traditional dietary pattern. These rates are even lower than those previously reported for Cypriot, Balearic and Greek adolescents [13,14,34]. It has been showed that adherence was strongly influenced by SES of parents of participants, and similar associations were found also in adult population [17].…”
Section: Discussionmentioning
confidence: 68%
“…Indeed, only 11% of adolescents living in rural areas and 9% of those living in urban, reported to have a good adherence (namely reaching the highest tertile of the index) to the traditional dietary pattern. These rates are even lower than those previously reported for Cypriot, Balearic and Greek adolescents [13,14,34]. It has been showed that adherence was strongly influenced by SES of parents of participants, and similar associations were found also in adult population [17].…”
Section: Discussionmentioning
confidence: 68%
“…The reasons for the gender difference are unknown but have been linked to immunological and hormonal factors, and/or to differences in gender-specific responses to environmental or occupational exposures [1114]. For example, children living on farms have a lower incidence of asthma [15], which has been related to modulation of the immune system by early life exposures, differences in physical activity levels or eating habits [16, 17]. However gender influences the impact of this exposure, i.e .…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that regular training could raise the threshold for respiratory symptoms . Recently, Kosti et al showed that leisure time activity was inversely associated with life‐time asthma in 10–12‐year‐old children. A study among Greek schoolchildren aged 10–12 years found an association between decreased physical activity measured by questionnaire and exercise‐induced bronchoconstriction .…”
Section: Discussionmentioning
confidence: 99%
“…4 Increasing activity levels in children may protect them against asthma. [5][6][7][8][9] But not all literature supports this hypothesis. 10,11 A recent review by Eijkemans et al 12 showed that high physical activity may lower the risk of asthma but results are heterogeneous across different populations (e.g., children vs. adults).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation